Dance as health intervention platform to raise awareness about negative body image through embodied knowledge among highschool students in General Santos City - Tripoli, Ferville Grace D. (2023)
Adolescents are most prone to body image concerns and intervention is needed to promote positive body attitude. This research production thesis explored the use of dance as a health intervention platform to raise awareness about the realities of negative body image, communicating through embodied knowledge among high school students in General Santos City. Through thematic analysis, this study used Social Learning Theory to establish the learning strategy of using dance performance as a symbolic model for knowledge generation. Integrating theories of symbolism and movement were also employed to translate data into relevant key messages for students to understand the lived experiences of individuals with body dissatisfaction through embodied knowledge. The phases of production were incorporated as guides in the actualization of the entire research production. Through a qualitative approach, the researcher interviewed fifteen individuals with negative body image to determine their lived experiences. The themes from their narratives were guided by Cognitive Behavioral Perspectives on Body Image. Findings revealed the themes of social media exposure to the ideal body, criticisms heighten the perceived negative body image, difficulty in self-presentation, suppression of self-expression, and coping processes on perceived negative body image were prominent from the lived experiences of the individuals with body dissatisfaction. Using dance as a health intervention platform, the study found that kinesic signals, space, repetitions, and embodied knowledge as learning language can be used to raise awareness of negative body image in the target audience.